15-Year survival rate of medial open wedge- high tibial osteotomy with TomoFix plate - Woon-Hwa Jung; Aniket Wagh; Minseok Seo; Ryohei Takeuchi (Journal of Orthopaedic Reports)
Background: Medial Open Wedge-High Tibial Osteotomy (MOW-HTO) has been universally accepted as treatment of choice for adults with medial joint Osteoarthritis (OA) and varus malalignment. TomoFix locking plate (Depuy Synthes) was popularised in the early 2000 which boasted about better fixation with lesser complications and early weight bearing. The main aim of this research is to study 15-year long term follow-up results of MOW-HTO with TomoFix plate and analyse the survival rate, complications, and possible risk factors. Materials and methods: Retrospective study enrolling 91 patients who underwent MOW-HTO with TomoFix between January to June 2009. Complications were noted. Clinical and radiological parameters were documented and analysed. 71 patients were followed up for 15 years. Kaplan Meier Survival Analysis and Log-Rank test were performed to evaluate the survival rate. Cox Regression Analysis was used to identify possible individual factors affecting the survival of the procedure. Results: Mean age of the study population was 59.83 ± 7.68 years. Fourteen (19.72 %) patients were converted to Total Knee Replacement (TKR), showing that the original procedure survived in 80.28 % of the patients at the end of 15 years. Kaplan Meier analysis estimated a survival rate of 75.75 % at the end of 20 years. Log-Rank test showed significant difference (p < 0.05) in survival between grade 3 and 4 of knee OA. According to Cox Regression Analysis, OA grade and Body Mass Index (BMI) were found to be the risk factors for HTO survival. The complication rate was 19.72 %, all of which could be managed conservatively. Conclusion: MOW-HTO with TomoFix plate proves to be an excellent biological option to conserve the native knee joint and should be the first choice of management in medial joint arthritis with varus malalignment in adults.